Human development in sacred landscapes: between ritual tradition, creativity and emotionality - Käppel, Lutz; Pothu, Basilikē (V&R unipress, 2015)
“Holy Landscape” is a term frequently used to describe a multidimensional phenomenon. What this actually comprises is hard to define. Precisely this question is addressed in this volume. The “holy landscape” depends on people’s Weltanschauung and is influenced by their respective culture and ethos. It is not just a question of religious buildings and rituals, nor is a mere matter of explicating terms such as “pure” and “impure”, magic and myths; it is about an expressive space in which the “ceremony and mood of rites and cults” take place.The contributions also deal with the emergence and continuing development of the term “holy landscape” and the changing expressions of religious mood.